Oral dexamethasone sodium phosphate solution significantly reduces pruritus and clinical lesions in feline hypersensitivity dermatitis: an open‐label study. Issue 5 (5th August 2021) - McClintock, Dayle; Austel, Michaela; Gogal, Robert M.; Banovic, Frane
Abstract : Background: There are no liquid oral glucocorticoids labelled for management of pruritus and clinical lesions of feline hypersensitivity dermatitis (feline HD). Hypothesis: First, to demonstrate that dexamethasone sodium phosphate (DexSP, DexajectSP, Henry Schein; Dublin, OH, USA; 4 mg/mL), an intravenous glucocorticoid, can be absorbed by healthy cats when administered orally. Second, to demonstrate the efficacy of orally administered DexSP for reducing pruritus and clinical lesions in patients with feline HD. Animals: Seven healthy and 12 client‐owned cats with HD. Methods and materials: Healthy cats were administered a single dose of 0.2 mg/kg DexSP p.o. and serum concentrations were measured using enzyme‐linked immunosorbent assay (ELISA). Feline HD patients were assessed with SCORing Feline Allergic Dermatitis (SCORFAD) and pruritus Visual Analog Scale (pVAS) at Visit 1 (V1) and after 20–31 days of receiving 0.2 mg/kg/day DexSP p.o. (V2). Complete blood cell counts, serum chemistry profile, and urinalysis were performed in 50% of feline HD patients at both visits. Results: Healthy cats had detectable serum concentrations of DexSP following oral administration; concentrations ranged from 0.7 to 92.3 ng/mL. Feline HD patients showed significant decreases in SCORFAD and pVAS scores from V1 to V2. Conclusions: DexSP was absorbed when administered orally to healthy cats and 0.2 mg/kg/day DexSP is an efficacious dose to rapidly improve the pruritus and clinical lesions associated with feline HD. Abstract : Background – There are no liquid oral glucocorticoids labelled for management of pruritus and clinical lesions of feline hypersensitivity dermatitis (feline HD). Hypothesis – First, to demonstrate that dexamethasone sodium phosphate (DexSP, DexajectSP, Henry Schein; Dublin, OH, USA; 4 mg/mL), an intravenous glucocorticoid, can be absorbed by healthy cats when administered orally. Second, to demonstrate the efficacy of orally administered DexSP for reducing pruritus and clinical lesions in patients with feline HD. Conclusions – DexSP was absorbed when administered orally to healthy cats and 0.2 mg/kg/day DexSP is an efficacious dose to rapidly improve the pruritus and clinical lesions associated with feline HD. Résumé: Contexte: Il n'existe pas de corticoïdes oral liquide labélisé pour la gestion du prurit et des lésions cliniques de la dermatite par hypersensibilité féline (HD). Hypothèses: D'abord, démontrer que la déxaméthasone sodium phosphate (DexSP, DexajectSP, Henry Schein ; Dublin, OH, USA ; 4 mg/mL), corticoïde intraveineux, peut être absorbé par les chats sains par voie orale. Ensuite, démontrer l'efficacité de DexSP administré oralement pour diminuer le prurit et les lésions cliniques des patients avec HD féline. Sujets: Sept chats de propriétaires sains et 12 avec HD. Matériels et methods: Les chats sains ont reçu une dose unique de 0, 2 mg/kg de DexSP po et les concentrations sériques ont été mesurées par ELISA. Les patients HD ont été évalués par SCORFAD (SCORing Feline Allergic Dermatitis) et pVAS (pruritus Visual Analog Scale) à visite 1 (V1) et après 20‐31 jours de DexSP po à 0, 2 mg/kg/jour (V2). Une numération formule, un profil biochimique, et une analyse d'urine ont été réalisés pour 50% des patients félins avec HD aux deux visites. Résultats: Les chats sains ont des concentrations sériques détectables pour DexSP suivant l'administration orale ; les concentrations variaient de 0, 7 à 92, 3 ng/mL. Les patients HD ont montré une diminution significative des scores SCORFAD et pVAS de V1 à V2. Conclusions: DexSP a été absorbé par voie orale aux chats sains et 0, 2 mg/kg/jour de DexSP est une dose efficace pour rapidement améliorer le prurit et les lésions cliniques associées à l'HD féline. Resumen: Introducción: no existen glucocorticoides orales líquidos etiquetados para el tratamiento del prurito y las lesiones clínicas de la dermatitis por hipersensibilidad felina (HD felina). Hipótesis: Primero, demostrar que el fosfato sódico de dexametasona (DexSP, DexajectSP, Henry Schein; Dublin, OH, USA; 4 mg/mL), un glucocorticoide intravenoso, puede ser absorbido por gatos sanos cuando se administra por vía oral. En segundo lugar, demostrar la eficacia de DexSP administrado por vía oral para reducir el prurito y las lesiones clínicas en pacientes con HD felina. Animales: siete gatos sanos y 12 con HD de propietarios particulares. Métodos y materiales: a los gatos sanos se les administró una dosis única de 0, 2 mg/kg de DexSP p.o. y las concentraciones séricas se midieron usando un ensayo de inmunoabsorción ligado a enzimas (ELISA). Los pacientes felinos con HD fueron evaluados con SCORing Feline Allergic Dermatitis (SCORFAD) y la escala análoga visual de prurito (pVAS) en la visita 1 (V1) y después de 20‐31 días de recibir 0, 2 mg/kg / día de DexSP p.o. (V2). Se realizaron hemogramas completos, perfil químico sérico y análisis de orina en el 50% de los pacientes felinos con HD en ambas visitas. Resultados: los gatos sanos tenían concentraciones séricas detectables de DexSP después de la administración oral; las concentraciones variaron de 0, 7 a 92, 3 ng/mL. Los pacientes felinos en HD mostraron disminuciones significativas en las puntuaciones de SCORFAD y pVAS de V1 a V2. Conclusiones: DexSP se absorbió cuando se administró por vía oral a gatos sanos y 0, 2 mg/kg/día de DexSP es una dosis eficaz para mejorar rápidamente el prurito y las lesiones clínicas asociadas con la HD felina. Zusammenfassung: Hintergrund: Es gibt keine zugelassenen Glukocortikoide zur oralen Anwendung beim Management von Pruritus und von klinischen Veränderungen der felinen Hypersensitivitätsdermatitis (feline HD). Hypothese: Erstens sollte gezeigt werden, dass Dexamethason Sodium Phosphat (DexSP, DexajectSP, Henry Schein; Dublin, OH, USA; 4 mg/mL), ein intravenös anwendbares Glukocortikoid von gesunden Katzen absorbiert werden kann, wenn es per os verabreicht wird. Zweitens sollte die Wirksamkeit von per os verabreichtem DexSP zur Reduzierung von Juckreiz und klinischer Läsionen bei Patienten mit feliner HD demonstriert werden. Tiere: Sieben gesunde Katzen und 12 Katzen in Privatbesitz mit HD. Methoden und Materialien: Den gesunden Katzen wurde eine einzige Dosis von 0, 2 mg/kg DexSP p.o . verabreicht und Serumkonzentrationen mittels Enzym‐linked Immunosorbent Assay (ELISA) gemessen. Katzen mit HD wurden beim ersten Besuch (V1) mittels SCORing Feline Allergic Dermatitis (SCORFAD) und Pruritus Visual Analog Scale (pVAS) und 20‐31 Tage nachdem sie 0, 2 mg/kg/Tag DexSP p.o . (V2) bekommen hatten, beurteilt. Blutbild, Serum Biochemie und eine Urinanalyse wurde bei 50% der Katzen mit HD bei beiden Vorstellungen durchgeführt. Ergebnisse: Gesunde Katzen zeigten feststellbare Serumkonzentrationen von DexSP nach der oralen Verabreichung; die Konzentrationen reichten von 0, 7 bis 92, 3 ng/mL. Die Katzen mit HD zeigten eine signifikante Abnahme bei SCORFAD und pVAS Werten vom ersten zum zweiten Besuch. Schlussfolgerungen: DexSP wurde absorbiert, wenn es gesunden Katzen per os verabreicht wurde. Eine Dosis von 0, 2 mg/kg/Tag an DexSP ist eine wirksame Dosis, um den Juckreiz und die klinischen Veränderungen, die mit feliner HD einhergehen, rasch zu verbessern! 要約: 背景: 猫過敏性皮膚炎 (feline HD) の掻痒および臨床病変の管理のためにラベル付けされた液体経口グルココルチコイドはない。 仮説: 本研究の目的は、第一に、静脈内グルココルチコイドであるデキサメタゾンリン酸エステルナトリウム (DexSP, DexajectSP, Henry Schein; Dublin, OH, USA; 4 mg/mL) を経口投与した場合、健常猫に吸収されることを実証することであった。第二に、猫HD患者における掻痒感および臨床病変の軽減に対する経口投与DexSPの有効性を実証することであった。 被験動物: 健常猫7頭およびオーナー所有HD猫12頭。 材料と方法: 健常猫に0.2mg/kgのDexSPを単回経口投与し、酵素結合免疫吸着法(ELISA)を用いて血清濃度を測定した。猫HD患者は、Visit 1(V1) および0.2 mg/kg/day DexSP 経口投与20‐31日後 (V2) に、SCORing Feline Allergic Dermatitis(SCORFAD) およびpruritus Visual Analog Scale(pVAS) で評価した。猫HD患者の50%において、両受診時に全血球数、血清化学プロファイル、および尿検査を実施した。 結果: 健常猫では、DexSPを経口投与することで、0.7˜92.3ng/mLの血清濃度が検出された。猫HD患者は、V1からV2にかけてSCORFADスコアおよびpVASスコアの有意な低下を示した。 結論: DexSPは健常猫に経口投与しても吸収され、0.2mg/kg/dayのDexSPは猫HDに伴う掻痒感や臨床病変を迅速に改善するのに有効な用量である。 摘要: 背景‐没有标记用于管理猫过敏性皮炎 (HD患猫) 瘙痒和临床病变的液体口服糖皮质激素。 假设‐首先, 证明地塞米松磷酸钠(DexSP, DexajectSP, Henry Schein;Dublin, OH, USA;4 mg/mL) (一种静脉糖皮质激素) 经口给药时可被健康猫吸收。其次, 证明口服DexSP对减少HD患猫瘙痒和临床病变的疗效。 动物–7只健康猫和12只客户拥有的HD患猫。 方法和材料‐健康猫单次经口给予0.2 mg/kg DexSP, 并使用酶联免疫吸附试验(ELISA)测定血清浓度。在访视1(V1)和接受0.2 mg/kg/天DexSP p.o.(V2)20‐31天后, 使用SCORing猫过敏性皮炎(SCORFAD)和瘙痒视觉模拟量表(pVAS)对HD患猫进行评估。在两次访视时, 在50%的HD患猫中进行了全血细胞计数、血清化学特征和尿液分析。 结果‐健康猫经口给药后可检测到DexSP的血清浓度; 浓度范围为0.7‐92.3 ng/mL。HD患猫显示SCORFAD和pVAS评分从V1至V2显著降低。 结论‐当经口给予健康猫时, DexSP被吸收, 0.2 mg/kg/天DexSP是快速改善猫HD的瘙痒和临床病变的有效剂量。 Resumo: Contexto: Não existem glicocorticóides orais líquidos registrados para o manejo do prurido e das lesões clínicas da dermatite por hipersensibilidade felina (HD felina). Hipótese: Primeiro, demonstrar que o fosfato de dexametasona sódica (DexSP, DexajectSP, Henry Schein; Dublin, OH, EUA; 4 mg/mL), um glicocorticóide intravenoso, pode ser absorvido por gatos saudáveis quando administrado por via oral. Em segundo lugar, para demonstrar a eficácia do DexSP administrado por via oral na redução do prurido e das lesões clínicas em pacientes com HD felina. Animais: Sete gatos saudáveis e 12 de clientes com HD felina. Métodos e materiais: Os gatos saudáveis receberam uma dose única de 0, 2 mg/kg de DexSP por via oral e as concentrações séricas foram mensuradas usando ensaio imunoenzimático (ELISA). Os pacientes felinos com HD foram avaliados utilizando o escore de dermatite alérgica felina ( SCORing Feline Allergic Dermatitis ‐ SCORFAD) e Escala Visual Analógica de prurido ( pruritus Visual Analog ‐ pVAS) na Visita 1 (V1) e após 20‐31 dias de receber 0, 2 mg/kg/dia de DexSP por via oral (V2). Realizou‐se hemograma, perfil químico sérico e urinálise foram realizados em 50% dos pacientes felinos com HD em ambas as visitas. Resultados: Gatos saudáveis apresentaram concentrações séricas detectáveis de DexSP após a administração oral; as concentrações variaram de 0, 7 a 92, 3 ng/mL. Os pacientes HD felina apresentaram reduções significativas nos escores SCORFAD e pVAS de V1 a V2. Conclusões: DexSP foi absorvido quando administrado por via oral a gatos saudáveis e 0, 2 mg/kg/dia DexSP é uma dose eficaz para melhorar rapidamente o prurido e as lesões clínicas associadas à HD felina.